The Effects of Plant-Based Feed Additives on Productive and Reproductive Performans in Poultry - ÖZKÖK, Arda Onur (MAS Journal of Applied Sciences, 2023)
The poultry sector is very important in order to meet the nutritional needs of the increasing world population. Compared to other farm animals, poultry has a shorter production period and is a relatively inexpensive source of protein. Feed additives are used to increase performance, improve product quality, and protect animal health in poultry. The demand for alternative additives has also increased with the prohibition of the use of growth promoting antibiotics in animal nutrition. Studies on plant-based feed additives have gained momentum because they are natural and more reliable. These additives, called phytobiotics, contain bioactive components. Some of these bioactive components have various properties such as antioxidant, antimicrobial, antiviral, and anti-inflammatory. In some in-vivo studies in poultry, it has been reported that various phytobiotics have positive effects on production and reproductive performance. In this review, general information about phytobiotics was given and their effects on production and reproductive performance were presented in poultry.